2020
DOI: 10.1101/2020.04.16.045880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First evidence of virus-like particles in the bacterial symbionts of Bryozoa

Abstract: 23Bacteriophage communities associated with humans and vertebrate animals have been 24 extensively studied, but the data on phages living in invertebrates remain scarce. In 25 fact, they have never been reported for most animal phyla. Our ultrastructural study 26 2 showed for the first time a variety of virus-like particles (VLPs) and supposed virus-27 related structures inside symbiotic bacteria in two marine species from the phylum 28 Bryozoa, the cheilostomes Bugula neritina and Paralicornia sinuosa. We als… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 89 publications
(98 reference statements)
5
15
0
Order By: Relevance
“…Their development following the total disappearance of bacteria in FBs indicates their bacteriophage nature. If so, our observations support the idea that viruses control the number of symbionts in their bryozoan host 20 , as has been reported in some insects 85,95 . 1): 1-distal zooidal bud and young autozooid with a polypide bud inside (no FBs); 2 -young autozooid with functional polypide and early developing FB; 3 -young autozooid with functional polypide and mature FB; 4 -autozooid with brown body, polypide bud and mature FB at initial stage of degradation; 5 -autozooid with brown body, functional polypide and FB at early-advanced stage of degradation; 6 -autozooid with brown body and FB at mid-advanced stage of degradation; 7 -autozooid with brown bodies and FB at late-advanced stage of degradation; 8 -autozooid with brown bodies and two FBs at terminal stage of degradation.…”
Section: Symbiont Population Dynamics In Dendrobeania Fruticosa and I...supporting
confidence: 90%
See 4 more Smart Citations
“…Their development following the total disappearance of bacteria in FBs indicates their bacteriophage nature. If so, our observations support the idea that viruses control the number of symbionts in their bryozoan host 20 , as has been reported in some insects 85,95 . 1): 1-distal zooidal bud and young autozooid with a polypide bud inside (no FBs); 2 -young autozooid with functional polypide and early developing FB; 3 -young autozooid with functional polypide and mature FB; 4 -autozooid with brown body, polypide bud and mature FB at initial stage of degradation; 5 -autozooid with brown body, functional polypide and FB at early-advanced stage of degradation; 6 -autozooid with brown body and FB at mid-advanced stage of degradation; 7 -autozooid with brown bodies and FB at late-advanced stage of degradation; 8 -autozooid with brown bodies and two FBs at terminal stage of degradation.…”
Section: Symbiont Population Dynamics In Dendrobeania Fruticosa and I...supporting
confidence: 90%
“…Our TEM study of FBs in D. fruticosa showed that they are not swollen parts of the funicular cords, as was stated by Vishnyakov with co-authors for B. neritina 20 . It is more likely that the funicular cords and processes of their cells contact the external cell layer of FBs.…”
Section: Funicular Bodies: Structure Function and Developmentsupporting
confidence: 82%
See 3 more Smart Citations